Educating Your Patient with Diabetes - Weinger, Katie; Carver, Catherine A. (Contemporary Diabetes, 2009)
Diabetes affects an estimated 20 million people in the United States, with many people remaining unaware that they suffer from the disease. While the number of diabetics continues to rise, the number of caregivers who specialize in diabetes treatment does not. In Educating Your Patient with Diabetes, Katie Weinger and Catherine Carver assemble commentary from a panel of leading diabetes practitioners and researchers and put together a highly readable guide to supplying patients with diabetes with the information and ability to successfully cope with their disease. The authors and editors provide substantive data on successful models of diabetes education and the process of educating diabetes sufferers. Additional chapters discuss diabetes in pregnancy, the challenge of weight and diabetes management in clinical practice, and diabetes education in geriatric populations. Timely and accessible, Educating Your Patient with Diabetes is a must have for all diabetes educators, physician assistants, nurses, and endocrinologists who endeavor to support their patients' diabetes self-care efforts and help them maximize the opportunities for patient learning.